2011
DOI: 10.1103/physreva.83.023424
|View full text |Cite
|
Sign up to set email alerts
|

Double ionization of atomic cadmium

Abstract: We have recorded the double photoionization spectrum of atomic Cd at four different photon energies in the range 40-200 eV. The main channel is single ionization and subsequent decay of excited Cd + states, some involving Coster-Kronig processes, whereas direct double ionization is found to be weak. The decay of the excited Cd + states shows a strong selectivity, related to the configuration of the final state. Double ionization leading to the Cd 2+ ground state is investigated in some detail and is found to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 40 publications
(46 reference statements)
5
12
0
Order By: Relevance
“…However, since the energy of all 4d 8 5s 2 states is below the ground-state energy of Cd 3+ , channel (6) can also be excluded. Our calculations also showed that some 4d 8 5s6s states have energies above the ground state energy of Cd 3+ , which agrees with previous findings in the study on double ionization [13]. We therefore also included several shakeup transitions in our computations, as discussed in following subsection.…”
Section: B 4d 9 Ground State Of CD 3+supporting
confidence: 77%
See 4 more Smart Citations
“…However, since the energy of all 4d 8 5s 2 states is below the ground-state energy of Cd 3+ , channel (6) can also be excluded. Our calculations also showed that some 4d 8 5s6s states have energies above the ground state energy of Cd 3+ , which agrees with previous findings in the study on double ionization [13]. We therefore also included several shakeup transitions in our computations, as discussed in following subsection.…”
Section: B 4d 9 Ground State Of CD 3+supporting
confidence: 77%
“…In using 200 eV photon energy, the removal of either a 4p or a 4s electron, both with additional shakeup processes during the photoionization is possible. Since this is the same photon energy as previously used for analyzing the double ionization spectrum of Cd [13], the present study can be regarded as a direct extension of that previous work. In adjusting the radiation intensity to a level which implied low ionization event probability per light pulse, the present experimental data were obtained in classical coincidence conditions.…”
Section: Methodssupporting
confidence: 49%
See 3 more Smart Citations